Transition-Metal-Free Insertion of Diazo Compounds, N-Arylsulfonylhydrazones or Ylides into Organoboronic Acids or Their Derivatives - Bao, Zhicheng; Wang, Jianbo (Synlett, 2023)
Insertion reactions of carbenes or ylides with organoboronic acids or their derivatives have emerged as valuable methods for coupling or homologation of organoboron compounds under metal-free conditions. The crucial steps of these reactions are coordination of the electron-rich carbon centers of the carbene precursors or ylides to the electron-poor boron center, followed by 1,2-migration of the corresponding tetracoordinated boron intermediates. This type of unique transformation provides an efficient method for the construction of C–C or C–X (X = H, B) bonds. Moreover, the C–B bonds generated by such transformations can be utilized as a handle for further derivatization or iterative homologations. In this Account, we summarize the developments in this arena according to the reactive diazo compound, N-arylsulfonylhydrazone or ylide species involved.1 Introduction2 Reactions with Diazo Compounds3 Reactions with N-Arylsulfonylhydrazones4 Reactions with Ylides5 Conclusion
Keywords: diazo compounds; ylides; N-tosylhydrazones; organoboronic acids; 1,2-migration